Electrophotographic belt and electrophotographic image forming apparatus

By introducing the second polyester resin and acrylic resin containing carboxyl -containing albatel -containing albatel -based resin in the hard coats used in electronic camera, the problem of insufficient tightness in the case of high curvature bending in the high curvature bending is solved, and excellent The tightness and scratch resistance ensure high -quality electronic photographic image output.

CN114585505BActive Publication Date: 2025-01-28CANON KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080072723.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-18
Filing Date
2020-10-05
Publication Date
2025-01-28
Estimated Expiration
2040-10-05

AI Technical Summary

Technical Problem

The existing electrophotographic tape is prone to insufficient adhesion between the hard coating and the base layer when bending with high curvature, resulting in the problem of peeling the hard coating from the base layer.

Method used

Adopt an electronic photographic belt composed of the first layer of polyester resin and the second layer containing a second polyester resin and an acrylic resin containing carboxyl -containing albatel -containing albatel -containing albatel groups. The carboxyl's acrylic resin improves the density of hard coats and the grassroots, and inhibits the degradation of scratch resistance.

Benefits of technology

In the case of high curvature bending, the excellent density and scratch resistance of hard coats and grassroots are ensured, and high -quality output of electronic image images is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114585505B_ABST
    Figure CN114585505B_ABST
Patent Text Reader

Abstract

Provided is an electrophotographic belt having a laminated structure, the electrophotographic belt having excellent scratch resistance and excellent adhesion between layers. The electrophotographic belt comprises a first layer and a second layer directly covering either an inner peripheral surface or an outer peripheral surface of the first layer, wherein: the first layer comprises a first polyester resin; and the second layer comprises a second polyester resin and an acrylic resin having a carboxyl group in each molecule.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to providing an electrophotographic belt for use in an electrophotographic image forming apparatus (hereinafter, referred to as an "electrophotographic apparatus") such as a copying machine and a printer, and the electrophotographic image forming apparatus. Background Art

[0002] In an electrophotographic image forming apparatus (hereinafter, also referred to as an "electrophotographic apparatus"), an electrostatic latent image bearing member such as a photosensitive drum is charged, and the charged electrostatic latent image bearing member is exposed to light, thereby forming an electrostatic latent image. Thereafter, the electrostatic latent image is developed with a toner subjected to frictional charging. The resulting toner image is transferred and fixed onto a recording medium such as paper, thereby forming a desired image on the recording medium. As a transfer system of such an electrophotographic apparatus, the following intermediate transfer system is known: an unfixed toner image on an electrostatic latent image bearing member such as a photosensitive drum is primarily transferred to an intermediate transfer member using current supplied from a transfer power source, and then the unfixed toner image is secondarily transferred from the intermediate transfer member to a recording medium.

[0003] Patent Document 1 and Patent Document 2 each disclose an electronic photographic belt that can be used as an intermediate transfer member and has a laminated structure, wherein the laminated structure includes a layer containing a thermoplastic resin (hereinafter, also referred to as a "base layer" or a "first layer"), and a layer containing an acrylic resin that is arranged on the outer peripheral surface or the inner peripheral surface of the base layer and has a higher hardness than the base layer.

[0004] Prior art literature

[0005] Patent Literature

[0006] PTL 1: Japanese Patent Application Publication No. 2006-330692

[0007] PTL 2: Japanese Patent Application Publication No. 2007-178750 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] The inventors conducted research and found that the electrophotographic belts described in Patent Documents 1 and 2 still have room for improving the adhesion of the hard coating layer to the base layer. In particular, with the recent miniaturization of the main body of the electrophotographic device, the electrophotographic belts began to be arranged in the electrophotographic device in a state where they were bent at a high curvature. Therefore, the inventors recognized the need to develop a technology for producing an electrophotographic belt that can effectively prevent the hard coating layer from being peeled off from the base layer even when the belt is bent at a high curvature.

[0010] At least one aspect of the present disclosure is directed to providing an electrophotographic belt having excellent scratch resistance and excellent adhesion between layers.

[0011] At least one other aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images.

[0012] Solutions for solving problems

[0013] According to at least one aspect of the present disclosure, there is provided an electrophotographic belt including a first layer and a second layer directly covering either an inner peripheral surface or an outer peripheral surface of the first layer, wherein the first layer includes a first polyester resin, and the second layer includes a second polyester resin and an acrylic resin containing a carboxyl group in the molecule.

[0014] According to at least one other aspect of the present disclosure, there is provided an electrophotographic image forming apparatus including a plurality of toner image bearing members and an intermediate transfer belt to which toner images are primarily transferred from the respective toner image bearing members, the intermediate transfer belt being the electrophotographic belt as described above.

[0015] Effects of the Invention

[0016] According to at least one aspect of the present disclosure, an electrophotographic belt having a laminated structure and excellent scratch resistance and excellent adhesion between layers can be obtained. According to at least one other aspect of the present disclosure, an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] [ Figure 1A ] is a schematic diagram of an electrophotographic belt according to an embodiment of the present disclosure, and is a perspective view of the electrophotographic belt having an annular shape.

[0018] [ Figure 1B ] is a schematic diagram of an electrophotographic belt according to one embodiment of the present disclosure, and is Figure 1A Enlarged axial cross-section of .

[0019] [ Figure 1C ] is a schematic diagram of an electrophotographic belt according to one embodiment of the present disclosure.

[0020] [ Figure 2 ] is a schematic diagram of an electronic photographic image forming apparatus according to another embodiment of the present disclosure.

[0021] [ Figure 3 ]yes Figure 2 FIG. 2 is an enlarged schematic diagram of the image forming unit 205 a.

[0022] [ Figure 4 ] is a schematic diagram of the outer peripheral surface of an electronic photography belt according to one embodiment of the present disclosure.

[0023] [ Figure 5 ] is a schematic diagram showing the structure of an embossing processing apparatus for forming grooves on the surface of an electrophotographic belt. DETAILED DESCRIPTION

[0024] In order to improve the adhesion of the hard coating layer to the base layer, the inventors attempted to make the base layer contain a polyester resin as a binder resin, and also make the hard coating layer contain a polyester resin containing an acrylic resin. This is intended to improve the adhesion of the hard coating layer to the base layer by making both the base layer and the hard coating layer contain a polyester resin to increase the affinity of the base layer and the hard coating layer to each other. As a result, the adhesion of the hard coating layer to the base layer can be improved. At the same time, adding a polyester resin to the hard coating layer deteriorates the scratch resistance of the hard coating layer.

[0025] The inventors further conducted studies to reduce the deterioration of scratch resistance due to the addition of a polyester resin to the hard coat layer, and found that introducing a carboxyl group into a molecule of an acrylic resin in the hard coat layer suppresses the deterioration of scratch resistance due to the addition of a polyester resin to the hard coat layer.

[0026] Specifically, in an electronic photographic belt including a base layer (hereinafter, also referred to as a "first layer") containing a first polyester resin as a binder resin and a hard coating layer (hereinafter, also referred to as a "second layer") directly covering either the front or back side of the first layer and containing an acrylic resin, the introduction of a second polyester resin and an acrylic resin containing a carboxyl group in the molecule into the hard coating layer can improve the adhesion of the second layer to the first layer while suppressing the deterioration of the scratch resistance of the second layer.

[0027] Here, the reason why, when a carboxyl group is present in the molecule of the acrylic resin in the second layer, the scratch resistance of the second layer is less likely to deteriorate even in the presence of the second polyester resin in the second layer is presumed to be that an interaction such as a hydrogen bond occurs between the terminal hydroxyl group of the second polyester resin and the carboxyl group of the acrylic resin, and a pseudo-crosslinking structure is formed between the acrylic resin and the second polyester resin.

[0028] The content ratio of the carboxyl group of the acrylic resin to the hydroxyl group of the second polyester resin in the second layer (carboxyl group / hydroxyl group) is preferably 1.0 or more and 12.0 or less, and particularly preferably 1.2 or more and 12.0 or less. Using the content ratio of the carboxyl group to the hydroxyl group within the aforementioned numerical range can more reliably form the above-mentioned pseudo-crosslinking structure in the second layer and better suppress the deterioration of the scratch resistance of the second layer caused by the introduction of the polyester resin into the second layer.

[0029] <Electronic Photography Belt>

[0030] Reference Figure 1A and 1B, an electrophotographic belt having an endless shape according to at least one embodiment of the present disclosure will be described in more detail below. Figure 1A It is a perspective view of the electrophotographic belt 100.

[0031] Figure 1B yes Figure 1A In the electrophotographic belt 100, the second layer 102 is present on the inner peripheral surface of the base layer 101, and the second layer is exposed from the inner peripheral surface of the electrophotographic belt. Although not shown in the figure, a third layer that contacts the photosensitive drum and other components may be provided on the outer peripheral surface of the base layer.

[0032] A voltage maintenance element such as a Zener diode is connected to the second layer via a member in contact with the second layer, so that the potential of the second layer can be kept constant. This makes it possible to cause a desired current to flow to all photosensitive drums via the second layer, producing an electrophotographic belt that can be used in an image forming apparatus that can perform not only secondary transfer but also primary transfer with a single transfer power source, as disclosed in Patent Document 2.

[0033] The electrophotographic belt has an annular shape because it is stretched by a plurality of rollers. The annular shape refers to a shape that can be stretched and rotated by a plurality of rollers, for example. In the annular belt shape, a seamless shape without a seam (seam) is preferred from the viewpoint of reducing unevenness in belt thickness. For example, the electrophotographic belt having the shape can be formed by connecting a sheet- or film-shaped material into a cylindrical shape, or by extruding a resin material into a cylindrical shape.

[0034] In order to be used in the above-mentioned compact and low-cost image forming apparatus, the volume resistivity of the electrophotographic belt at an applied voltage of 250 V measured in a standard environment (temperature 23° C. and humidity 50%) is preferably 1×10 9 Ω·cm or more and 1×10 11 Preferably, the surface resistivity of the inner peripheral surface is lower than that of the outer peripheral surface, and the surface resistivity measured from the inner peripheral surface is 4.0×10 6 Ω / □ or less. Such a surface resistivity makes it possible to reduce the occurrence of image defects such as blanks due to insufficient transfer voltage required for primary transfer of the toner image on the outer surface of each photosensitive drum to the transfer belt.

[0035] Hereinafter, examples of constituent materials of each layer of the electrophotographic belt and a method for producing the electrophotographic belt will be described. The method for producing the electrophotographic belt is not specified in the following examples.

[0036] [Base layer (first layer)]

[0037] The base layer contains a polyester resin (first polyester resin) as a binder resin. Examples of the base layer include an endless belt formed of a cylindrically connected semiconductive film of a resin containing a first polyester resin containing a conductive agent; and a cylindrical seamless belt.

[0038] (First polyester resin)

[0039] The first polyester resin may be prepared by polycondensation of a dicarboxylic acid component and a dihydroxy component, polycondensation of an oxycarboxylic acid component or a lactone component, or polycondensation using a plurality of components thereof. The polyester resin may be a homopolyester or a copolyester.

[0040] Examples of dicarboxylic acid components include aromatic dicarboxylic acids, alicyclic dicarboxylic acids, aliphatic dicarboxylic acids, and derivatives of these dicarboxylic acids. Examples of aromatic dicarboxylic acids include aromatic dicarboxylic acids having carbon numbers of 8 or more and 16 or less (C8 to C16) in the molecule. Specific examples thereof include terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acids such as 2,6-naphthalene dicarboxylic acid, diphenyl dicarboxylic acids, diphenyl ether dicarboxylic acids, diphenyl methane dicarboxylic acids, and diphenyl ethane dicarboxylic acids. Examples of alicyclic dicarboxylic acids include C4-C10 cycloalkane dicarboxylic acids, such as cyclohexane dicarboxylic acids. Examples of aliphatic dicarboxylic acids include C4-C12 aliphatic dicarboxylic acids, such as succinic acid, adipic acid, azelaic acid, and sebacic acid. Examples of derivatives of these dicarboxylic acids include derivatives (e.g., lower alkyl esters, such as dimethyl esters, anhydrides, and acyl halides such as acyl chlorides) that can form esters. These dicarboxylic acid components can be used alone or in combination of two or more thereof. From the viewpoint of crystallinity and heat resistance, preferred dicarboxylic acid components are aromatic dicarboxylic acids, with terephthalic acid, isophthalic acid and naphthalene dicarboxylic acid being more preferred.

[0041] Examples of dihydroxy components include aliphatic diols, alicyclic diols and aromatic diols. Examples of aliphatic diols include C2-C10 alkylene glycols, such as ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol and hexanediol. Examples of alicyclic diols include C4-C12 alicyclic diols, such as cyclohexanediol or cyclohexanedimethanol. Examples of aromatic diols include C6-C20 aromatic diols, such as hydroquinone, resorcinol, dihydroxybiphenyl, naphthalene diol, dihydroxydiphenyl ether and 2,2-bis (4-hydroxyphenyl) propane (bisphenol A). Other examples thereof include alkylene oxide adducts of aromatic diols (e.g., C2-C4 alkylene oxide adducts of bisphenol A). Other examples further include polyoxyalkylene glycols (e.g., polyoxy C2-C4 alkylene glycols, such as diethylene glycol, polyoxyethylene glycol, polyoxypropylene glycol, and polytetramethylene ether glycol). The dihydroxy component may be a derivative capable of forming an ester (e.g., a component substituted with an alkyl, alkoxy, or halogen). These dihydroxy components may be used alone or in combination of two or more thereof. Among these dihydroxy components, from the viewpoints of, for example, crystallinity and heat resistance, it is preferred to use an alkylene glycol (particularly a C2-C4 alkylene glycol) or an alicyclic diol.

[0042] Examples of the hydroxycarboxylic acid component include hydroxybenzoic acid, hydroxynaphthoic acid, diphenylene hydroxycarboxylic acid, 2-hydroxypropionic acid, and derivatives of these hydroxycarboxylic acids. These hydroxycarboxylic acid components may be used alone or in combination of two or more thereof.

[0043] Examples of the lactone component include C3-C12 lactones such as propiolactone, butyrolactone, valerolactone, and caprolactone (eg, ε-caprolactone). These lactone components may be used alone or in combination of two or more thereof.

[0044] In addition, a multifunctional monomer may be used in combination within the range of maintaining crystallinity and heat resistance. Examples of the multifunctional monomer include polycarboxylic acids such as trimellitic acid, trimesic acid, and pyromellitic acid; and polyols such as glycerol, trimethylolpropane, trimethylolethane, and pentaerythritol. Polyesters having a branched or cross-linked structure produced by using such a multifunctional monomer may also be used.

[0045] As the first polyester resin, a polyester resin obtained by polycondensing the above-mentioned components (dicarboxylic acid component and dihydroxy component, hydroxycarboxylic acid component, lactone component or multiple components thereof) can be used. From the viewpoints of their crystallinity, heat resistance and other properties, at least one selected from poly(alkylene terephthalate), poly(alkylene naphthalate), and block / random copolymers of poly(alkylene terephthalate) and poly(alkylene isophthalate). Examples of copolymers include block copolymers and random copolymers. From the viewpoints of crystallinity and heat resistance, the number of carbon atoms of the alkylene group in each of poly(alkylene terephthalate), poly(alkylene isophthalate) and poly(alkylene naphthalate) is preferably 2 or more and 16 or less. More preferably, at least one selected from poly(ethylene terephthalate), block / random copolymers of poly(ethylene terephthalate) and poly(ethylene isophthalate), and poly(ethylene naphthalate).

[0046] The first polyester resin may be a blend or alloy of two or more. Specific examples of poly(ethylene naphthalate) include commercially available TN-8050SC (trade name, manufactured by Teijin Limited) and TN-8065S (trade name, manufactured by Teijin Limited). An example of poly(ethylene terephthalate) is commercially available TR-8550 (trade name, manufactured by Teijin Limited). An example of a copolymer of poly(ethylene terephthalate) and poly(ethylene isophthalate) is commercially available PIFG30 (trade name, manufactured by Bell Polyester Products, Inc.).

[0047] The intrinsic viscosity of the first polyester resin is preferably 1.4 dl / g or less, more preferably 0.3 dl / g or more and 1.2 dl / g or less, still more preferably 0.4 dl / g or more and 1.1 dl / g or less. An intrinsic viscosity of 1.4 dl / g or less can effectively prevent a decrease in fluidity during molding. An intrinsic viscosity of 0.3 dl / g or more can effectively ensure high strength and high durability. The intrinsic viscosity of the polyester resin is a value measured by using o-chlorophenol as a diluting solvent for the polyester resin, setting the concentration of the o-chlorophenol solution of the polyester resin to 0.5 mass % and setting the temperature to 25°C.

[0048] The first polyester resin is preferably 50% by mass or more, particularly 60% by mass or more, and more preferably 70% by mass or more based on the total mass of the base layer. At 50% by mass or more, degradation of the durability of the electrophotographic belt can be effectively prevented.

[0049] (Conductive agent)

[0050] In the base layer, non-ionic or ionic conductive agents can be used as conductive agents. As conductive agents, polymer or low molecular conductive agents can be used. Examples of usable polymer non-ionic conductive agents include poly (ether ester amide), poly (ethylene oxide-epichlorohydrin), or poly (ether ester). Examples of usable polymer ionic conductive agents include quaternary ammonium-containing acrylic acid ester polymers as cationic conductive agents; and polystyrene sulfonic acid as anionic conductive agents. Examples of usable low molecular non-ionic conductive agents include ether-containing derivatives and ether-ester-containing derivatives. Examples of usable low molecular ionic conductive agents include primary ammonium salts to tertiary ammonium salts and quaternary ammonium salts and their derivatives as cationic conductive agents; and carboxylates, sulfate ester salts, sulfonates, phosphate ester salts and their derivatives as anionic conductive agents. These polymer and low molecular conductive agents can be used alone or in combination of two or more thereof. Among them, from the viewpoint of their heat resistance and conductivity, quaternary ammonium salts, sulfonates, and poly (ether ester amide) are preferred.

[0051] Additives such as a plasticizer, an antioxidant, a decomposition inhibitor, a crystallization controller, a roughness adjuster, a crosslinking agent, a pigment, a filler, and an elastomer may be added to the base layer as necessary.

[0052] (Method of forming base layer)

[0053] The base layer can be formed, for example, by the following method. When a thermoplastic resin is used as the resin, an ionic surfactant as a conductive agent, a resin, and additives as needed are mixed together and melt-kneaded with, for example, a twin-screw kneader to prepare a semiconductive pellet. Then, the pellet can be extruded into a sheet, a film, or a seamless belt by melt extrusion to obtain a semiconductive film. The forming can also be completed by hot pressing or injection molding. The formed preform can be stretched and blown to produce a semiconductive film. The thickness of the base layer is preferably 20 μm or more and 500 μm or less, more preferably 30 μm or more and 150 μm or less.

[0054] Regarding the resistance of the base layer thus obtained, the volume resistivity at an applied voltage of 250 V is preferably 1.0×10 8 Ω·cm or more and 1.0×10 12 Ω·cm or less. The surface resistivity is preferably 1.0×10 8 Ω / □ or more and 1.0×10 12 Ω / □ or less. Controlling the resistance within the semi-conductive region can suppress defects in the transferred image caused by insufficient transfer voltage due to overcharging in a low-humidity environment or during continuous driving.

[0055] [Second floor]

[0056] The second layer contains a second polyester resin and an acrylic resin (hereinafter, also referred to as a "binder resin"). The surface resistivity of the second layer at an applied voltage of 10 V at a temperature of 23° C. and a humidity of 50% is preferably 4.0×10 6 Ω / □, more preferably 1.0×10 6 Ω / □. The lower limit of the surface resistivity is not limited to a specific value. When the surface resistivity is within the above range, a primary transfer current equivalent to that of a primary transfer using a plurality of transfer power supplies of the prior art can be supplied to each photosensitive drum. The surface resistivity is a value measured by a method for measuring the surface resistivity of the second layer, as described below.

[0057] From the viewpoint of flexural resistance, the thickness of the second layer is preferably 0.05 μm or more and 10 μm or less, and more preferably 0.1 μm or more and 5 μm or less. Considering the above thickness, the binder resin is preferably a binder resin soluble in a solvent so that a thin layer containing the binder resin can be formed or a thin layer containing a binder resin raw material can be formed.

[0058] The average hardness of the region in the second layer, which extends from a position of 10% of the thickness of the second layer in the thickness direction from the outermost surface to a position of 20% of the thickness of the second layer in the thickness direction from the outermost surface, may preferably be 0.10 GPa or more, more preferably 0.15 GPa or more, the average hardness being measured on the outer surface of the second layer by a nanoindentation method using a Berkovich type indenter. The region near the outermost surface extending from the outermost surface to a position less than 10% of the thickness of the second layer from the outermost surface is easily affected by the measurement environment such as vibration of the indenter. The region extending from a position greater than 20% of the thickness of the second layer from the outermost surface to the base layer is easily affected by the base layer. For these reasons, these regions are excluded, and the average hardness in the region of 10-20% of the thickness of the second layer is calculated. By controlling the hardness of the second layer so that the average hardness in the region is 0.15 GPa or more, even when the image is continuously output, the occurrence of physical deterioration such as wear or abrasion due to friction with other sliding members (such as a transfer roller) in the electrophotographic apparatus can be suppressed. The upper limit of the average hardness in the region of the second layer is preferably, but not necessarily, 0.50 GPa or less because physical damage to a sliding member mounted on a general electrophotographic device can be suppressed. That is, the average hardness in the region of the second layer is more preferably 0.15 GPa or more and 0.50 GPa or less, and particularly preferably 0.20 GPa or more and 0.40 GPa or less. Examples of the method for increasing the hardness include a method in which the molecular weight of the polyester resin is increased; and a method in which a high-hardness filler or a crosslinking agent is added.

[0059] (Second polyester resin)

[0060] From the viewpoint of strength, the second polyester resin used for the second layer preferably contains at least an aromatic polyester resin. Examples thereof include polyester resins containing monomer units derived from phthalic acid selected from the group consisting of terephthalic acid, phthalic acid and isophthalic acid. Specific examples thereof include copolymers containing ethylene terephthalate units and ethylene phthalate units; and copolymers containing ethylene terephthalate units and ethylene isophthalate units. Other examples thereof include copolymers containing ethylene phthalate units and ethylene isophthalate units. These copolymers may be any of block copolymers and random copolymers. A mixture of two or more copolymers of blended and alloyed (alloyed) may be used. The second layer preferably contains a plurality of polyesters having different chemical structures. In this case, the non-crystallinity is increased to provide better adhesion to the base layer. The chemical structure of the polyester resin can be determined by extracting the polyester from the second layer using an appropriate method such as dissolving in a solvent, followed by separation, followed by identification using pyrolysis-GC / MS, IR, NMR, and elemental analysis.

[0061] In addition to the above-mentioned second polyester resin, the second layer may further contain other additives within the range that does not impair the effects of the embodiment. Specific examples thereof include molybdenum disulfide, boron nitride, silicon nitride, layered clay minerals, silicone particles, fluororesin particles, silicone oil, fluorinated oil, perfluoropolyether, crystallization control agent, and crosslinking agent. These additives may be used alone or in combination of two or more thereof.

[0062] When a crosslinking agent such as diisocyanate is added with the raw material for the second polyester resin, the second polyester resin is a polymer containing a urethane bond in the molecule (polyester urethane resin). From the viewpoint of improving the hardness of the second layer, the second polyester resin is preferably a polyester urethane resin.

[0063] From the viewpoint of heat resistance, the glass transition temperature (Tg) of the polyester resin used for the second layer is preferably higher than 60°C. Below 60°C, printing in a high temperature environment or a temperature rise in the image forming apparatus during continuous printing may soften the second layer and cause fusion with a member such as a transfer roller in contact with the second layer, which may cause image defects. The Tg of the binder resin can be calculated by separating the resin from the second layer and then observing the endothermic peak and the shift of the baseline during the temperature rise using a differential scanning calorimeter (DSC). The hydroxyl value of the polyester resin used for the second layer will be described in detail in Evaluation 5 below.

[0064] The weight average molecular weight (Mw) of the above polyester resin is preferably, but not necessarily, within the range of 40,000 or more and 200,000 or less. The weight average molecular weight of the polyester resin being 40,000 or more results in better hardness of the second layer. The weight average molecular weight (Mw) of the polyester resin being 200,000 or less results in good solubility in solvents and suppresses an increase in the viscosity of the coating, thereby making it easier to obtain a desired thickness.

[0065] (Acrylic resin)

[0066] The acrylic resin used for the second layer contains a carboxyl group in its molecule.

[0067] An example of the acrylic resin is an acrylic resin containing a structural unit represented by the structural formula (1).

[0068] Structural formula (1)

[0069] [Chemistry 1]

[0070]

[0071] In the structural formula (1), R1 to R3 are each independently a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms.

[0072] A solvent-soluble polymer type is preferred because the second layer can be formed by applying and drying a coating material containing an acrylic resin.

[0073] Specific examples of acrylic resins include acrylic resins containing monomer units such as acrylate, methacrylate, methyl acrylate, methyl methacrylate, ethyl acrylate, and ethyl methacrylate and containing carboxyl groups in the molecule. These polymers may be any of block copolymers and random copolymers. A mixture of two or more copolymers blended or alloyed may be used.

[0074] The acid value (mgKOH / g) of the carboxyl-containing acrylic resin is preferably, but not necessarily, 70 mgKOH / g or more. Using an acid value of 70 mgKOH / g or more can suppress the reduction of hardness even when an acrylic resin is used in combination with a polyester resin in the second layer, thereby providing good scratch resistance. The method for determining the acid value will be described in detail in Evaluation 5 below.

[0075] The weight average molecular weight (Mw) of the above-mentioned acrylic resin is preferably, but not necessarily, in the range of 5,000 or more and 200,000 or less. The weight average molecular weight of the acrylic resin of 5,000 or more leads to better hardness of the second layer. The weight average molecular weight (Mw) of the acrylic resin of 200,000 or less leads to good solubility in solvents and suppresses the increase in viscosity of the coating, thereby making it easier to obtain the desired thickness. For example, commercially available solvent-free acrylic polymer "ARUFON UC-3000" series (trade name, manufactured by Toagosei Co., Ltd.) can be used as the acrylic resin. Specific examples thereof include "ARUFON UC-3000", acid value = 74 mgKOH / g, and Mw = 10,000; "ARUFON UC-3080", acid value = 230 mgKOH / g, and Mw = 14,000; "ARUFON UC-3510", acid value = 70 mgKOH / g, and Mw = 2,000; "ARUFON UC-5080", acid value = 170 mgKOH / g, and Mw = 17,000; and "ARUFON UC-5022", acid value = 235 mgKOH / g, and Mw = 14,000.

[0076] From the viewpoint of improving scratch resistance, the content of the acrylic resin in the second layer is preferably, but not necessarily, 3% by mass or more, particularly preferably 5% by mass or more, based on the second layer. From the viewpoint of adhesion to the polyester resin in the first layer, the content of the acrylic resin in the second layer is preferably 25% by mass or less, particularly preferably 20% by mass or less, based on the second layer.

[0077] (Conductive particles)

[0078] Specific examples of the electron conductive agent that may be included in the second layer to adjust the conductivity of the second layer are described below.

[0079] Examples thereof include carbon black, graphite, carbon nanotubes (hereinafter, also referred to as “CNTs”), carbon microcoils, graphene, zinc oxide, zinc antimonate, tin oxide, tin-doped indium oxide (ITO), antimony-doped tin oxide (ATO), and conductive polymers such as polyaniline, polypyrrole, and polythiophene.

[0080] Among them, "Ketjen Black" (registered trademark) is preferred due to high conductivity. The carbon black content of the second layer is preferably, but not necessarily, 6% by mass or more to adjust the surface resistivity to the above value. From the viewpoint of more reliably suppressing the deterioration of physical properties such as cracks and wear caused by friction with other sliding members (e.g., transfer rollers and tension rollers), the carbon black content of the second layer is preferably 15% by mass or less. That is, the carbon black content of the second layer is preferably 6% by mass or more and 15% by mass or less, and more preferably 9% by mass or more and 13% by mass or less.

[0081] The carbon black content can be determined by the amount of residue left after the pyrolysis reaction of the second layer. Among the materials constituting the second layer, carbon black has the highest pyrolysis temperature. Therefore, a sample of the second layer is scraped from the electrophotographic belt and weighed, and treated in an air atmosphere at a temperature higher than or equal to the decomposition temperature of the binder resin and lower than the decomposition temperature of carbon black using a thermogravimetric analyzer (TGA) to promote the pyrolysis reaction. From this, the content can be calculated. Regarding specific conditions, the temperature is increased to 500°C at a heating rate of 20°C / min and then maintained for several hours to promote the pyrolysis reaction of materials other than carbon black. When the weight reduction rate is less than or equal to 1% / hour, it can be judged that the pyrolysis reaction has been completed. The carbon black content can be calculated by the amount of carbon black added during the formation of the second layer.

[0082] (Method for Forming Second Layer)

[0083] The second polyester resin and the acrylic resin are preferably soluble in a solvent such as methyl ethyl ketone, methyl isobutyl ketone, or cyclohexanone. The reason for this is that the second layer can be formed by applying a coating containing a polyester resin and an acrylic resin, which is advantageous in terms of cost.

[0084] Specifically, for example, the second layer forming method includes the steps of applying a second layer forming coating material containing a polyester resin, an acrylic resin, a solvent dissolving the resin, and carbon black to the surface of the base layer to form a coating film, and then removing the solvent.

[0085] The polyester resin can be obtained from raw materials such as dicarboxylic acids and diols by transesterification and polycondensation. Alternatively, a commercially available coating containing a polyester resin can be used. In addition, as required, the second layer forming coating may contain additives such as a leveling agent. As a leveling agent, any known leveling agent can be appropriately selected and used. The resulting second layer forming coating is applied to the inner or outer peripheral surface of the base layer by a coating method such as dip coating, spray coating, ring coating or roller coating. The solvent can then be removed by drying to form a second layer as a coating film.

[0086] [Third floor]

[0087] In order to prevent, for example, close contact and adhesion with other contact members such as a photosensitive drum and a cleaning blade, the third layer 103 may be provided in such a manner that the third layer 103 is in direct contact with the surface of the base layer that is not covered by the second layer, in the inner and outer peripheral surfaces of the base layer (see Figure 1C ). The third layer may include a resin. Considering the thickness of the third layer, the resin is preferably, but not necessarily, soluble in a solvent and capable of forming a thin layer. Examples of resins include soluble polyimides, polyester resins, and curable urethanes and acrylic resins. These may be used alone or in combination. The same coating as the coating used to form the second layer may also be used to form the third layer.

[0088] In addition to the above-mentioned resins, filler particles and lubricants are preferably added to the third layer as additives. Specifically, the following can be exemplified. Examples thereof include aluminum oxide, titanium dioxide, silicon dioxide, zirconium oxide, zinc oxide, zinc antimonate, tin oxide, tin-doped indium oxide (ITO), antimony-doped tin oxide (ATO), molybdenum disulfide, boron nitride, silicon nitride and layered clay minerals. Other examples include silicone particles, fluororesin particles such as polytetrafluoroethylene (PTFE) particles, carbon black, graphite, carbon nanotubes, carbon microcoils and graphene. In addition, silicone oil, fluorinated oil and perfluoropolyether are exemplified. Among them, from the viewpoint of reducing friction, PTFE particles are preferred. These additives can be used alone or in combination of two or more thereof.

[0089] When using PTFE particles, based on 100 mass parts of the resin in the third layer, the PTFE particle content of the third layer is preferably more than 5 mass parts and less than 60 mass parts, more preferably more than 10 mass parts and less than 50 mass parts. The use of the PTFE particle content within the above range can prevent adhesion and close fit with other contact members. As required, conductive agents, curing agents, antioxidants, ultraviolet absorbers, pH adjusting agents, crosslinking agents and pigments, etc. can be added to the third layer.

[0090] The outer surface of the third layer on the opposite side to the side facing the base layer preferably has a groove. When the outer surface has a groove, the contact area with a member (hereinafter, also referred to as a "contact member") such as a cleaning blade that contacts the outer surface can be reduced, thereby further reducing the frictional resistance between the outer surface and the contact member.

[0091] Examples of usable groove forming methods include, but are not limited to, a method in which the inner circumferential surface of an electrophotographic belt containing a third layer is supported by a core, and then the electrophotographic belt is rotated in a circumferential direction to polish the outer surface while the outer surface of the third layer is brought into contact with a lapping film containing abrasive grains; and an imprinting process in which a mold pre-processed into a desired shape is brought into contact with the outer surface.

[0092] Figure 4 An electrophotographic belt 400 having an endless shape according to at least one other embodiment of the present disclosure is shown, in which the outer surface of the third layer has grooves.

[0093] A plurality of grooves 401 are provided on the outer peripheral surface of the electrophotographic belt 400 .

[0094] Each groove 401 is formed so as to intersect with a line drawn assuming that it extends in a direction perpendicular to the circumferential direction of the electrophotographic belt. More specifically, each groove 401 is arranged in the circumferential direction of the electrophotographic belt 400 and is non-parallel to the circumferential direction. The minor angle θ formed between each groove 401 and the circumferential direction is preferably greater than 0° and less than ±3°. More preferably, the angle θ is less than ±1°. When the angle of the groove 401 relative to the circumferential direction is 0°, that is, when the groove 401 extends parallel to the circumferential direction of the electrophotographic belt, the portion of the cleaning blade that contacts the area clamped between two adjacent grooves 401 of the electrophotographic belt (hereinafter, also referred to as the "land portion") is fixed, and only the portion can be worn to cause poor cleaning.

[0095] The outer peripheral surface of the belt for electrophotography is preferably composed of only a first region 402 in which the number of grooves in a direction perpendicular to the circumferential direction is n, and a second region 403 in which the number of grooves in a direction perpendicular to the circumferential direction is greater than n. In this case, the first region and the second region are arranged alternately in the circumferential direction. The number n of the grooves 401 can be any number as long as the toner removal cleaning can be stably performed, and the number is preferably 2,000 to 120,000. The presence of more than 2,000 grooves can reduce the area of ​​the portion of the cleaning blade that contacts the portion where the grooves 401 are not provided, thereby reducing the friction generated between the cleaning blade and the belt for electrophotography 400. The presence of less than 120,000 grooves can better transfer the toner on the grooves 401.

[0096] The number of grooves in the second region is preferably (2n-10) or more and (2n+10) or less. When the number of grooves in the second region is (2n-10) or more, the position of the contact portion of the cleaning blade at the boundary between the first region and the second region can be stably changed. When the number of grooves in the second region is (2n+10) or less, the toner on the grooves can be better transferred.

[0097] Regarding each groove, from the viewpoint of toner removal cleaning, the intervals between adjacent grooves are preferably, but not necessarily, substantially equal. Equal intervals can reduce local blade wear.

[0098] The circumferential length of the second region is preferably 0.01 to 50 mm. Each groove is discontinuous in the circumferential direction, and the second region may include the ends of each groove. When the circumferential length of the second region is 50 mm or less, the toner on the groove can be better transferred.

[0099] The depth of each groove 401 is preferably 0.10 μm or more and less than 5.0 μm, more preferably 0.20 μm or more and less than 2.0 μm. When the depth of the groove is within the above range, the contact state between the cleaning blade and the electrophotographic belt can be stabilized for a long period of time.

[0100] From the viewpoint of crack and flex resistance, the thickness of the third layer is preferably 0.05 μm or more and 10 μm or less, and more preferably 0.1 μm or more and 5 μm or less.

[0101] <Electronic Photographic Equipment>

[0102] Reference Figure 2 A color electrophotographic apparatus according to an embodiment of the present disclosure will be described in which a belt for electrophotography according to an embodiment of the present disclosure is used as an intermediate transfer belt.

[0103] The electrophotographic apparatus includes an image forming unit 205a for forming a yellow image, an image forming unit 205b for forming a magenta image, an image forming unit 205c for forming a cyan image, and an image forming unit 205d for forming a black image. Each image forming unit includes a photosensitive drum 205-1, which is a toner image bearing member configured to bear a toner image on its surface. Each photosensitive drum contacts the outer peripheral surface of an intermediate transfer belt 200 formed of a belt for electrophotography according to an embodiment of the present disclosure.

[0104] The intermediate transfer belt 200 is supported by three rollers, a driving roller / secondary transfer counter roller 201 and tension rollers 202 and 203. The driving roller / secondary transfer counter roller 201 includes a rubber layer provided on a surface layer and having a high friction resistance so as to drive the intermediate transfer belt 200. The rubber layer is conductive and has a volume resistivity of 1.0×10 5Ω·cm or less. The driving roller / secondary transfer counter roller 201 and the secondary transfer roller 204 together form a secondary transfer portion with the intermediate transfer belt 200 disposed therebetween. The tension roller 202 includes a rubber layer. The rubber layer is conductive and has a volume resistivity of 1.0×10 5 Ω·cm or less. The tension roller 203 may be a metal roller. The secondary transfer roller 204 is pressed against the driving roller / secondary transfer counter roller 201 via the intermediate transfer belt 200 disposed therebetween. As the secondary transfer roller 204, a roller having a volume resistivity of 1.0×10 7 Ω·cm or more and 1.0×10 9 The tension rollers 202 and 203 and the secondary transfer roller 204 are driven to rotate by the intermediate transfer belt 200 .

[0105] The secondary transfer roller 204 is in contact with the outer peripheral surface of the intermediate transfer belt 200 except for the secondary transfer process. The power supply 214 applies voltage to the secondary transfer roller 204 so that current flows from the secondary transfer roller 204 to each photosensitive drum included in the image forming unit via the intermediate transfer belt 200. This causes the toner image carried by each photosensitive drum to be primarily transferred from the photosensitive drum to the intermediate transfer belt 200. In other words, the secondary transfer roller 204 functions as a current supply member that supplies current to the intermediate transfer belt 200 when the toner image carried by the photosensitive drum is primarily transferred to the outer peripheral surface of the intermediate transfer belt 200. As described above, in the electronic photographic apparatus, the power supply for primary transfer and the power supply for secondary transfer are shared.

[0106] Taking the image forming unit 205a as an example, the electrophotographic apparatus will be described in detail below.

[0107] Figure 3 2 is an enlarged schematic diagram of the image forming unit 205a. The image forming unit 205a includes a photosensitive drum 206a as an image bearing member, and is driven to rotate at a predetermined process speed. Around the photosensitive drum 206a, a charging roller 207a as a charging member, a developing member 209a containing a toner 208a, and a drum cleaning member 210a are arranged. Around the photosensitive drum 206a, an exposure member 211a is further arranged between the charging roller 207a and the developing member 209a. The photosensitive drum 206a is charged by the charging roller 207a, and the charged electrostatic latent image bearing member is exposed by the exposure member 211a, thereby forming an electrostatic latent image (toner image). Thereafter, the electrostatic latent image is developed by the toner 208a frictionally charged in the developing member 209a. The developed image is transferred to the intermediate transfer belt 200 located at a position facing each image forming unit by applying a primary transfer voltage (hereinafter referred to as "primary transfer").

[0108] Similarly, in the image forming units 205b, 205c, and 205d, primary transfer is performed in synchronization with the rotation of the intermediate transfer belt 200, thereby forming a four-color composite toner image. At this time, it is preferred that one or more metal rollers 212 as primary transfer counter members are arranged between the image forming units 205b and 205c at positions facing the image forming units with the intermediate transfer belt 200 interposed therebetween. By forming the primary transfer portion using the metal rollers 212 that press the intermediate transfer belt 200 against the image forming units facing the intermediate transfer belt 200, the primary transfer width (nip) can be widened and stabilized.

[0109] A recording medium 213 such as paper is fed to a position on the intermediate transfer belt 200, which is located downstream of the position of the fourth image forming unit 205d. A secondary transfer roller 204 (secondary transfer member) is provided at the same position. The gap between the intermediate transfer belt 200 and the secondary transfer roller 204 and its vicinity, where the toner image on the intermediate transfer belt 200 is transferred to the recording medium, is referred to as a secondary transfer portion. Figure 2 As shown, the secondary transfer section preferably includes a roller gap between the driving roller / secondary transfer counter roller 201 and the secondary transfer roller 204. When the non-image portion immediately before the composite toner image formed on the intermediate transfer belt 200 reaches the secondary transfer section, a voltage with a polarity opposite to that of the toner is applied from a voltage power source 214 that supplies current to the secondary transfer roller 204. Then, when the recording medium 213 is moved along the path of the secondary transfer roller 204, the recording medium 213 is moved along the path of the secondary transfer roller 204. Figure 2 When the intermediate transfer belt 200 passes through the secondary transfer section in the direction indicated by the middle arrow Vf, the four-color composite toner image on the intermediate transfer belt 200 is transferred to the recording medium 213 in one operation. This transfer is called "secondary transfer". The recording medium 213 subjected to secondary transfer is subjected to a fixing process in a fixing unit (not shown) to form a color image. The residual toner on the intermediate transfer belt 200 that has not been subjected to secondary transfer is scraped off by a cleaning blade 215, which is in contact with the belt surface provided with the tension roller 202 at any given time, and is collected in a waste toner box 216. In this way, the surface of the intermediate transfer belt 200 is restored to its initial state.

[0110] In the electrophotographic apparatus according to one embodiment of the present disclosure, a transfer voltage required for primary transfer in addition to a transfer voltage required for secondary transfer is obtained from a voltage power supply 214. The intermediate transfer belt 200 includes, for example, a second layer on the inner peripheral surface of the belt. Figure 2As shown, each metal roller 212 in contact with the inner peripheral surface of the intermediate transfer belt 200 is connected to a Zener diode 217 as a constant voltage element and is grounded. Therefore, the voltage applied from the voltage power supply 214 makes the potential of the second layer of the intermediate transfer belt constant in the circumferential direction. As a result, substantially the same potential difference is adopted between the intermediate transfer belt and the photosensitive drums of each image forming unit 205a, 205b, 205c and 205d, and substantially the same current flows to the photosensitive drum. This enables primary transfer. The resistance of the recording medium itself changes according to environmental changes such as changes in temperature and humidity during image formation, and therefore, the secondary transfer voltage preferably changes within a predetermined range.

[0111] In the electrophotographic apparatus, in the case where the secondary transfer voltage changes, for example, a higher secondary transfer voltage, since the Zener diode 217 is connected, current flows when the Zener potential is exceeded. This enables the potential of the second layer to be maintained at a constant level, thereby stabilizing the primary transferability. Specifically, it is preferred that the applied voltage of the voltage power supply 214 is 1,000 to 3,500V, and the Zener potential is 220 to 300V. According to this embodiment, since the above-mentioned transfer structure is provided, primary transfer and secondary transfer can be stably performed by one transfer power supply.

[0112] Example

[0113] Hereinafter, Examples and Comparative Examples will be described.

[0114] In the following examples and comparative examples, the materials in the coating may be diluted with a solvent or dispersed in a solvent. Unless otherwise specified, the amount (parts by mass) of each material is based on the amount of non-volatile components and means the amount excluding the solvent (volatile component).

[0115] Table 1 shows materials used for the second layers of the electrophotographic belt Nos. to 17 according to Examples 1 to 7, Comparative Examples 1 to 9, and Reference Example 1. Table 2 shows the evaluation results of the electrophotographic belt Nos. 1 to 17.

[0116] [Example 1]

[0117] (Formation of the grass-roots)

[0118] The following materials were provided as raw materials for forming the base layer.

[0119] Poly(ethylene naphthalate) as a polyester resin (trade name: Teonex TN8050SC, manufactured by Teijin Limited) (hereinafter, referred to as "PE (1)")

[0120] Copolymer of poly(ethylene terephthalate) and poly(ethylene isophthalate) (trade name: PIFG30, manufactured by Bell Polyester Products, Inc.) (hereinafter, referred to as "PE (2)")

[0121] Poly(ether ester amide) (trade name: TPAE-10HP-10, manufactured by T&K Toka Co., Ltd.) (hereinafter, referred to as "PEEA")

[0122] Potassium perfluorobutane sulfonate (trade name: Eftop KFBS, manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.) (hereinafter, referred to as "KFBS")

[0123] The melting point of PE (1) is 262°C.

[0124] The above PE (1) / PE (2) / PEEA / KFBS was mixed in a ratio of 72 / 8 / 18 / 2 (mass %), and then melt-kneaded at 290° C. for 5 minutes using a twin-screw extruder (trade name: TEX30α, manufactured by The Japan Steel Works, Ltd.) to prepare a resin mixture of PE (1), PEEA, and KFBS. The resulting resin mixture was granulated with a cutter (trade name: Fan-Cutter, manufactured by Hoshi Plastic Co., Ltd.) to produce pellets of the resin mixture (pellet size: long diameter 3 mm×short diameter 2 mm). The resulting pellets were dried at 140° C. for 6 hours. The dried pellets of the resin mixture were fed to the hopper of an injection molding machine (trade name: SE180D, manufactured by Sumitomo Heavy Industries, Ltd.). The barrel temperature was set to 290° C. The pellets were melted under the stirring of the screw and injection molded into a mold to form a preform having a test tube shape. The obtained preform was placed in a blow molding machine and blow-molded with a stretch rod and air power in a blow mold maintained at a mold temperature of 110°C, a preform temperature of 155°C, an air pressure of 0.3 MPa, and a stretch rod speed of 1,000 mm / s to produce a blow-molded bottle. Both ends of the blow-molded bottle were cut off to obtain an endless belt-shaped substrate for an electrophotographic belt. The thickness of the substrate was 70 μm.

[0125] (Preparation of polyester resin for second layer)

[0126] 194 parts by mass of dimethyl terephthalate, 194 parts by mass of dimethyl isophthalate, 239 parts by mass of ethylene glycol and 38 parts by mass of diethylene glycol were added to the autoclave. Next, 0.2 parts by mass of tetrabutyl titanate as a catalyst was placed in the autoclave, and the transesterification reaction was carried out at 190° C. to 220° C. for 5 hours. The pressure in the reaction system was reduced to 0.67 kPa (5 mmHg) within 20 minutes, while the temperature was raised to 280° C. during this period. The polycondensation reaction was carried out at 13.3 Pa (0.1 mmHg) and 280° C. for 60 minutes to obtain a polyester (1) having monomer units derived from isophthalic acid and terephthalic acid. DSC measurement revealed that the glass transition temperature of the polyester (1) thus prepared was 65° C.

[0127] (Formation of the Second Layer)

[0128] The following raw materials were used for the formation of the second layer.

[0129] ARUFON UC-3000 (trade name, acid value = 74 mgKOH / g, weight average molecular weight Mw = 10,000, manufactured by Toagosei Co., Ltd.) (hereinafter, also referred to as "acrylic resin (1)") which is commercially available and contains a carboxyl group as an acrylic resin

[0130] ·The above polyester (1)

[0131] Carbon black (trade name: MHI Black #273, manufactured by Mikuni-Color Ltd.) (hereinafter, also referred to as "carbon")

[0132] The above-mentioned acrylic resin (1) / polyester (1) / carbon is mixed in a ratio of 8.1 / 81.3 / 10.6 (mass %). The resulting mixture is diluted with methyl ethyl ketone to a solid content concentration of 15 mass %. The mixture is stirred with a stirrer to prepare a uniform second layer forming coating. The coating is uniformly applied to the inner peripheral surface of the base layer by spraying and dried at 70°C for 5 minutes. This produces an electronic photographic belt No. 1 containing a 2 μm thick second layer on the inner peripheral surface of the base layer. Then, the electronic photographic belt No. 1 is subjected to evaluations 1 to 6 described below.

[0133] <Evaluation 1: Measurement of Average Hardness of Second Layer>

[0134] The hardness of the second layer was measured using a microindentation hardness tester (trade name: Nanoindenter G200, manufactured by Agilent Technologies) with a Bohr type indenter. The measurement area was an area 10% to 20% in the thickness direction from the outermost surface of the second layer, and the average hardness in the area was calculated. The results are shown in Table 2. In Table 2, "N" indicates that evaluation was impossible because the acrylic resin and the polyester resin were phase separated and the surface of the coating film was significantly uneven.

[0135] <Evaluation 2: Measurement of resistivity>

[0136] The surface resistivity of the second layer was measured using a resistivity meter (trade name: Hyresta UP MCP-HT450, manufactured by Mitsubishi Chemical Analytic Co., Ltd.) in accordance with Japanese Industrial Standard (JIS) K 6911. The surface resistivity of the second layer was measured as follows: In an environment of a temperature of 23°C and a relative humidity of 50%, a URSS probe was brought into contact with the second layer, and a value at an applied voltage of 10V and a measuring time of 10 seconds was defined as a measured value. Four points spaced 90° apart in the circumferential direction of the second layer were measured, and the average value of these measured values ​​was calculated. The volume resistivity of the electronic photographic belt including the base layer and the second layer was measured as follows: In the above environment, a UR probe was brought into contact with the outer peripheral surface of the belt, and a value at an applied voltage of 250V and a measuring time of 10 seconds was defined as a measured value. Four points spaced 90° apart in the circumferential direction of the electronic photographic belt were measured, and the average value of these measured values ​​was calculated. The results are shown in Table 2.

[0137] <Evaluation 3: Evaluation of scratch resistance>

[0138] In addition to applying the coating prepared in the embodiments and comparative examples to a glass plate instead of the above-mentioned base layer, a second layer is formed in the same manner as described above. The scratch resistance of each second layer is evaluated as follows: steel wool (#0000) is brought into contact with the surface of the sample maintained on a reciprocating abrasion tester and reciprocated 50 times under a load of 500g and a reciprocating speed of 10cm / s. Before and after the test, the glossiness at an angle of 60° relative to the surface of the coating film is measured using a gloss meter (IG-320, manufactured by Horiba, Ltd). The percentage of the quotient of the gloss level after the test divided by the gloss level before the test is defined as the gloss maintenance rate and is used as an indicator of scratch resistance. The measurement results are evaluated based on the following evaluation criteria.

[0139] Grade A (very good scratch resistance): gloss maintenance rate is 75% or more.

[0140] · Grade B (good scratch resistance): The gloss maintenance rate is 55% or more and less than 75%.

[0141] · Grade C (poor scratch resistance): gloss maintenance rate is less than 55%.

[0142] <Evaluation 4: Evaluation of Adhesion>

[0143] The transfer tapes produced in the examples and comparative examples were evaluated according to JIS K5400. A line reaching the interface between the base layer and the second layer was drawn with a cutting tool to make a grid of 100 squares each measuring 1 mm×1 mm. An adhesive tape (trade name: Cellophane Tape, manufactured by Nichiban Co., Ltd.) was adhered thereto, and then removed by pulling in a direction at an angle of 90°. The results were evaluated according to the following criteria.

[0144] ·Rank A (very good: no peeling was observed)

[0145] · Grade B (Good: Minor peeling was observed at a portion of the intersection of the cuts)

[0146] Grade C (partial or complete peeling is observed along the cut line)

[0147] <Evaluation 5: Measurement of Acid Value and Hydroxyl Value>

[0148] The acid value of each acrylic resin and the hydroxyl value of each polyester resin were determined by performing acid value titration analysis and hydroxyl value titration analysis in accordance with Japanese Industrial Standard (JIS) K0070 and calculating using formulas (1) and (2).

[0149] Formula (1)

[0150] Hydroxyl value (mgKOH / g) = {(V1-V0) × f1 × 0.5 × 56.11} / S1 + acid value

[0151] In formula (1),

[0152] S1: mass of the collected sample (g);

[0153] V0: the amount of 0.5 mol / L potassium hydroxide alcohol solution required for the blank test (mL);

[0154] V1: the amount of 0.5 mol / L potassium hydroxide alcohol solution required for the actual test (mL); and

[0155] f1: coefficient of 0.5 mol / L potassium hydroxide alcohol solution (1.005).

[0156] Formula (2)

[0157] Acid value (mgKOH / g) = {(V3-V2) × f2 × 0.1 × 56.11} / S2

[0158] In formula (2),

[0159] S2: mass of the collected sample (g);

[0160] V2: the amount of 0.1 mol / L potassium hydroxide alcohol solution required for the blank test (mL);

[0161] V3: the amount (mL) of 0.1 mol / L potassium hydroxide alcohol solution required for the actual test; and

[0162] f2: Coefficient of 0.1 mol / L potassium hydroxide alcohol solution (1.006).

[0163] The hydroxyl value titration analysis will be described in detail below.

[0164] About 2 g of the sample to be measured and 5 mL of the acetylation reagent are placed in a 200 mL conical flask. An air condenser is connected thereto. The mixture is reacted in an oil bath at 100 ° C for 1 hour. After natural cooling at room temperature, 1 mL of water is added. The mixture is heated again in an oil bath at 100 ° C for another 10 minutes. After natural cooling, the inside of the air condenser and the inner wall surface of the flask are rinsed with ethanol. The resulting solution is diluted with 30 mL of pyridine. Using 1% phenolphthalein solution as an indicator, titration is performed with 0.5 mol / L potassium hydroxide alcohol solution (f=1.005). The time point when the solution turns light red is defined as the end point.

[0165] A blank test was also performed in the same manner. The hydroxyl value was calculated from the above formula. An acetylating agent was prepared by weighing 20 g of acetic anhydride in a flask and adding pyridine thereto to make 100 mL.

[0166] The acid value titration analysis will be described in detail below.

[0167] Into a 100mL conical flask, place 2g of sample, 30mL of ethanol, and 30mL of 2-butanone. Dissolve the sample at room temperature. Use 1% phenolphthalein solution as an indicator and titrate with 0.1mol / L potassium hydroxide alcohol solution (f=1.006). The time point when the solution turns red is defined as the end point. Perform a blank test in the same manner. Calculate the acid value from the above formula.

[0168] The calculated acid value and hydroxyl value are calculated values ​​per 1 g of the measured acrylic resin and polyester resin. Therefore, the product of the value given in Table 1 and the resin content is calculated, and the content ratio of "carboxyl group / hydroxyl group" is calculated.

[0169] Based on the above Evaluation 5, Table 1 shows the acid values ​​and hydroxyl values ​​of the binder resins used for the second layer of the transfer belts according to the following Examples and Comparative Examples.

[0170] <Evaluation 6: Evaluation of image quality>

[0171] Each of the obtained electrophotographic belts is used as Figure 2 An intermediate transfer belt of an electrophotographic image forming apparatus of the structure shown in FIG. was used to form an electrophotographic image, and the presence or absence of image defects caused by secondary transfer was observed. Letter-sized (width: 216 mm) plain paper (trade name: Business 4200, manufactured by Xerox Corp., basis weight: 75 g / m 2 ) is used as paper. Regarding the printing mode, a secondary color image formed by superimposing solid images of two colors of colorants output in a single-sided printing mode is used. Here, each secondary color image refers to an image with an average concentration of 200% for red (R), green (G), and blue (B). After outputting 150,000 images, the first output image (hereinafter, also referred to as "initial") and the 150,000th output image are evaluated. After outputting the above number of sheets, the electronic photographic belt is taken out from the image forming apparatus, and then the surface of the second layer is visually observed. Whether peeling of the second layer from the base layer occurs and scratches on the second layer are evaluated based on the following criteria.

[0172] · Rank A: No peeling of the second layer from the base layer or scratches on the second layer were observed, and the output image was good.

[0173] Rank C: Peeling of the second layer from the base layer or scratches on the second layer were observed, and image defects due to band unevenness were observed in a portion of the output image corresponding to the relevant site.

[0174] · Rank N: Image defects due to insufficient transfer voltage were observed.

[0175] [Example 2]

[0176] Electrophotographic Belt No. 2 was produced in the same manner as in Example 1 except that the polyester (1) used for the second layer in Example 1 was changed to a polyester-type polyurethane resin containing monomer units derived from terephthalic acid and isophthalic acid (trade name: Vylon UR1400, manufactured by Toyobo Co., Ltd.) (hereinafter, also referred to as "Polyester (2)"). DSC measurement showed that the glass transition temperature of Polyester (2) was 83° C. Electrophotographic Belt No. 2 was subjected to the above-mentioned evaluations 1 to 6.

[0177] [Example 3]

[0178] Electrophotographic Belt No. 3 was produced in the same manner as in Example 2 except that the ratio of acrylic resin (1) / polyester (2) / carbon was changed to 14.9 / 74.5 / 10.6 (mass %). The obtained Electrophotographic Belt No. 3 was subjected to the above-mentioned evaluations 1 to 6.

[0179] [Example 4]

[0180] Electrophotographic Belt No. 4 was produced in the same manner as in Example 3 except that the ratio of acrylic resin (1) / polyester (2) / carbon was changed to 20.6 / 68.8 / 10.6 (mass %). The obtained Electrophotographic Belt No. 4 was subjected to the above-mentioned evaluations 1 to 6.

[0181] [Example 5]

[0182] Electrophotographic Belt No. 5 was produced in the same manner as in Example 1 except that the polyester (1) used in the second layer of Example 1 was changed to a polyester-type polyurethane resin containing monomer units derived from phthalic acid and isophthalic acid (trade name: Vylon UR8200, manufactured by Toyobo Co., Ltd.) (hereinafter, also referred to as "Polyester (3)"). DSC measurement showed that the glass transition temperature of Polyester (3) was 73° C. The obtained Electrophotographic Belt No. 5 was subjected to the above-mentioned evaluations 1 to 6.

[0183] [Example 6]

[0184] Electrophotographic Belt No. 6 was produced in the same manner as in Example 1 except that the polyester (1) used in the second layer of Example 1 was changed to a polyester-type polyurethane resin containing monomer units derived from terephthalic acid and isophthalic acid (trade name: Vylon UR4800, manufactured by Toyobo Co., Ltd.) (hereinafter, also referred to as "Polyester (4)"). DSC measurement showed that the glass transition temperature of Polyester (4) was 106° C. The obtained Electrophotographic Belt No. 6 was subjected to the above-mentioned evaluations 1 to 6.

[0185] [Example 7]

[0186] By the same method as in Example 1, the same coating material as that for forming the second layer described above was applied to the outer peripheral surface of the electrophotographic belt No. 1 produced in Example 1, thereby providing an electrophotographic belt 500 including the third layer.

[0187] use Figure 5The embossing processing equipment shown in forms a groove on an electrophotographic belt 500. A mold having a diameter of 50 mm and a length of 250 mm and composed of carbon steel (S45C) subjected to chemical nickel plating is provided as a cylindrical mold 501 for groove formation. The mold has a spiral continuous convex pattern provided by cutting. The convex pattern has a convex height of 3.5 μm, a convex bottom length of 2.0 μm, a convex top length of 0.2 μm, and a convex pattern interval of 20 μm. The angle of the convex pattern of the cylindrical mold 501 for groove formation relative to the circumferential direction is 0.1°. The cylindrical mold 501 for groove formation includes an internally embedded box heater and can be heated.

[0188] The belt 500 for electrophotography is mounted to the outer periphery of the cylindrical belt holding core 503 (circumference: 712 mm). The cylindrical mold 501 for groove formation and the cylindrical belt holding core 503 can both rotate around their own axes. Both the mold and the core rotate at 30 mm / sec (the directions of rotation are opposite to each other), and the cylindrical mold 501 for groove formation heated to 130°C is pressed against the cylindrical belt holding core 503 with a pressing force of 8.0 MPa while keeping their axial center lines parallel to each other. By this method, the convex pattern of the cylindrical mold 501 for groove formation is transferred to the outer peripheral surface of the belt 500 for electrophotography, that is, the outer surface of the third layer. When the rotation of the cylindrical belt holding core 503 is slightly passed through 1 circle (corresponding to 1 mm), the cylindrical mold 501 for groove formation is separated from the outer surface of the belt 500 for electrophotography. In this way, the belt No. 7 for electrophotography having grooves on the outer peripheral surface is produced.

[0189] Since the convex pattern of the groove forming cylindrical mold 501 has a spiral shape, during the groove formation, after the groove forming cylindrical mold rotates one circle, the starting end and the end of each groove are not connected to each other. Therefore, the outer surface of the electronic photographic belt No. 7 includes a first area in which the number of grooves in a direction perpendicular to its circumferential direction is n and a second area in which the number of grooves in a direction perpendicular to its circumferential direction is greater than n. Specifically, the outer surface of the obtained electronic photographic belt No. 7 consists of a first area and a second area. The number of grooves in the direction perpendicular to the circumferential direction in the first area is 12,200. The number of grooves in the direction perpendicular to the circumferential direction in the second area is 24,401. The length of the circumferential direction of the second area is 1.1 mm. The small angle θ formed between each groove and the circumferential direction is 0.1°. The above evaluations 1 to 6 were performed on the produced electronic photographic belt No. 7.

[0190] [Example 8]

[0191] The third layer-forming coating material was prepared as described below.

[0192] A mixture was obtained by mixing acrylic resin (1) / polyester (1) at a ratio of 9.1 / 90.9 (mass %). The mixture was diluted with methyl ethyl ketone to have a solid content concentration of 15 mass %. The obtained mixture was stirred with a stirrer to prepare a coating material for forming a third layer.

[0193] The coating for forming the third layer was uniformly applied to the outer peripheral surface of the base layer opposite to the surface covered by the second layer of the electrophotographic belt No. 1 produced in Example 1 by a spray coating method, and dried at 70° C. for 5 minutes. In this way, a third layer having a thickness of 2 μm was formed on the outer peripheral surface of the base layer. Then, grooves were formed on the outer surface of the third layer in the same manner as in Example 7 to provide an electrophotographic belt No. 8. The above-mentioned evaluations 1 to 6 were performed on the produced electrophotographic belt No. 8. Evaluations 1 to 4 and evaluation 6 were performed on the third layer in the same manner as for the second layer.

[0194] [Comparative Example 1]

[0195] Electrophotographic Belt No. 9 was produced in the same manner as in Example 1 except that acrylic resin (1) was not used and the ratio of polyester (1) / carbon was changed to 89.4 / 10.6 (mass %). The obtained Electrophotographic Belt No. 9 was subjected to the above-mentioned Evaluations 1 to 6.

[0196] [Comparative Example 2]

[0197] Electrophotographic Belt No. 10 was produced in the same manner as in Example 1 except that the acrylic resin (1) was changed to a non-functional acrylic resin (trade name: ARUFON UP-1170; produced by Toagosei Co., Ltd.) (hereinafter, referred to as "acrylic resin (2)"). The obtained electrophotographic Belt No. 10 was subjected to the above-mentioned Evaluations 1 to 6.

[0198] [Comparative Example 3]

[0199] Electrophotographic Belt No. 11 was produced in the same manner as in Comparative Example 2, except that the acrylic resin (2) was changed to a hydroxyl-containing acrylic resin (trade name: ARUFON UH-2000; manufactured by Toagosei Co., Ltd.) (hereinafter, referred to as "acrylic resin (3)"). The obtained electrophotographic Belt No. 11 was subjected to the above-mentioned evaluations 1 to 6.

[0200] [Comparative Example 4]

[0201] Electrophotographic Belt No. 12 was produced in the same manner as in Example 1 except that the polyester (1) was not used and the ratio of acrylic resin (1) / carbon was changed to 89.4 / 10.6 (mass %). The obtained Electrophotographic Belt No. 12 was subjected to the above-mentioned Evaluations 1 to 6.

[0202] [Comparative Example 5]

[0203] Electrophotographic Belt No. 13 was produced in the same manner as in Comparative Example 2 except that the polyester (1) was not used and the ratio of acrylic resin (2) / carbon was changed to 89.4 / 10.6 (mass %). The obtained Electrophotographic Belt No. 13 was subjected to the above-mentioned Evaluations 1 to 6.

[0204] Table 2 shows the evaluation results

[0205] Table 1

[0206]

[0207] Table 2

[0208]

[0209] The evaluation results shown in Table 2 are described below.

[0210] The electrophotographic belts Nos. 1 to 8 according to Examples 1 to 8 each of which second layers contained a carboxyl-containing acrylic resin and a polyester resin were both good in scratch resistance and interlayer adhesion, and the quality of the 150,000th output image was also good.

[0211] Even in the case where the polyester resin is present in the second layer, the presence of the carboxyl group in the molecule of the acrylic resin in the second layer is unlikely to deteriorate the scratch resistance of the second layer. The reason for this is presumed to be that an interaction such as a hydrogen bond occurs between the terminal hydroxyl group of the polyester resin and the carboxyl group of the acrylic resin, and a pseudo-crosslinking structure is formed between the acrylic resin and the polyester resin.

[0212] Compared with the electrophotographic belt No. 1, the electrophotographic belts Nos. 2, 5, and 6 containing the urethane group-containing polyester resin (polyesters (2) to (4)) have high hardness and particularly good scratch resistance.

[0213] In the electrophotographic belt No. 9 according to Comparative Example 1 in which the second layer contained a polyester resin without a carboxyl-containing acrylic resin, the adhesion was good, but the scratch resistance was insufficient. In the 150,000th output image, an image defect due to scratches on the inner peripheral surface of the electrophotographic belt was observed. The electrophotographic belts Nos. 12 and 13 in which each of the second layers contained no polyester resin had insufficient adhesion to the base layer. In each of the 150,000th output images, an image defect due to unevenness caused by peeling of the second layer from the base layer on the inner peripheral surface of the electrophotographic belt was observed.

[0214] The present invention is not limited to the above-described embodiments, and various changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, in order to disclose the scope of the present invention, the following claims are attached.

[0215] This application claims priority from Japanese Patent Application No. 2019-191116, filed on October 18, 2019, the entire contents of which are incorporated herein by reference.

Claims

1. An electrophotographic belt, characterized in that: It contains: a first layer and a second layer, wherein the second layer directly covers any one of the inner peripheral surface and the outer peripheral surface of the first layer, The first layer comprises a first polyester resin, and The second layer comprises a second polyester resin and an acrylic resin containing a carboxyl group in the molecule. The acid value of the acrylic resin containing a carboxyl group in the molecule is 70 mgKOH / g or more.

2. The electrophotographic belt according to claim 1, wherein the first polyester resin is at least one of poly(ethylene terephthalate) and poly(ethylene naphthalate).

3. The electrophotographic belt according to claim 1 or 2, wherein the acrylic resin containing a carboxyl group in the molecule comprises a structural unit represented by formula (1): [Chemistry 1] Structural formula (1) in, In the structural formula (1), R1 to R3 are each independently hydrogen or a hydrocarbon group having 1 to 3 carbon atoms.

4. The electrophotographic belt according to claim 1 or 2, wherein the second polyester resin is a polyester polyurethane resin. 5 . The electrophotographic belt according to claim 1 , wherein a content ratio of carboxyl groups of the acrylic resin to hydroxyl groups of the polyester resin contained in the second layer, ie, carboxyl group / hydroxyl group, is 1.0 or more and 12.0 or less.

6. The electrophotographic belt according to claim 1 or 2, wherein the electrophotographic belt has an endless shape. 7 . The electrophotographic belt according to claim 1 , wherein the second layer has a thickness of 0.05 μm or more and 10 μm or less.

8. The electrophotographic belt according to claim 1 or 2, further comprising a third layer, wherein the third layer directly covers a surface of the first layer opposite to the surface covered by the second layer, among the inner peripheral surface and the outer peripheral surface of the first layer, Wherein the third layer comprises grooves on the outer surface.

9. The electrophotographic belt according to claim 8, wherein the grooves are provided on the outer surface of the third layer, extend in the circumferential direction of the electrophotographic belt, and are non-parallel to the circumferential direction.

10. An electrophotographic belt according to claim 1 or 2, wherein the average hardness of a region in the second layer is greater than or equal to 0.10 GPa, the region extending from a position at which the thickness of the second layer is 10% of the thickness of the second layer in the thickness direction from the outermost surface to a position at which the thickness of the second layer is 20% of the thickness of the second layer in the thickness direction from the outermost surface, and the average hardness is measured on the outer surface of the second layer by a nanoindentation measurement method using a Bosch-type indenter.

11. The electrophotographic belt according to claim 1 or 2, wherein the second layer contains conductive particles, and the surface resistivity of the second layer is 4.0 × 10 6 Ω / square or less.

12. The electrophotographic tape according to claim 1 or 2, wherein the volume resistivity of the electrophotographic tape is 1×10 9 Ω·cm or more and 1 × 10 11 Ω·cm or less.

13. An electrophotographic image forming device, characterized in that: It contains: A plurality of toner image bearing members and an intermediate transfer belt to which toner images are primarily transferred from the respective toner image bearing members, the intermediate transfer belt being a belt for electrophotography according to any one of claims 1 to 12.

14. The electrophotographic image forming apparatus according to claim 13, further comprising: A current supply member in contact with the intermediate transfer belt, and a power source configured to apply a voltage to the current supply member, wherein the colorant image is transferred once from each of the colorant image bearing members to the intermediate transfer belt by applying a voltage from the power source to the current supply member so that a current passes through the intermediate transfer belt in a circumferential direction.

15. The electrophotographic image forming apparatus according to claim 14, wherein the current supply member is in contact with an outer peripheral surface of the electrophotographic belt.

Citation Information

Patent Citations

  • Electrophotographic belt, electrophotographic apparatus, method for producing electrophotographic belt and intermediate transfer belt

    JP2006330692A

  • Belt for image forming apparatus and image forming apparatus provided with same

    JP2007178750A

  • Radiation detection device and inspection device

    JP2019191116A

  • Conductive endless belt, its manufacturing method, and image forming apparatus using same

    JP2006184787A

  • Cylindrical member, transfer device, and image forming device

    JP2013041121A